ANIMART Learning Media Based on Education Through Art for Elementary School Children Material on Learning About Animals - Aulya Indah Puspita; Deasylina Da Ary (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop, determine the feasibility, and test the effectiveness of ANIMART learning media based on Education Through Art in improving the learning outcomes of third-grade students on the subject of animals. This study uses the ADDIE model research and development method. Data collection techniques were carried out through observation, interviews, questionnaires, documentation, as well as pre-tests and post-tests. Data analysis used descriptive analysis, expert validity testing, paired sample t-test, and N-Gain calculation. The results showed that the ANIMART media was designed in the form of animated videos that integrated the concept of animal movement with dance elements through the Education Through Art approach, so that students could learn visually, kinesthetically, and enjoyably. This media is unique in that it combines IPAS material with movement art activities that encourage active student involvement. Validation results by media experts, IPAS material experts, and dance material experts show that the media is in the highly feasible category after one revision. The effectiveness test results show a significant difference between the pre-test and post- test scores (Sig. 0.002 < 0.05) with an N-Gain value of 0.57, which is classified as moderate. Thus, ANIMART media is quite effective in improving student learning outcomes